2020
DOI: 10.1186/s43058-020-00006-8
|View full text |Cite
|
Sign up to set email alerts
|

From novice to expert: a qualitative study of implementation facilitation skills

Abstract: Background: It is widely reported that facilitation can aid implementation of evidence-based practices. Although scholars agree that facilitators need a diverse range of skills, only a few retrospective studies have identified some of these. During the test of a facilitation strategy within the context of a VA initiative to implement evidence-based care delivery models, we documented the skills an expert external facilitator transferred to two initially novice internal regional facilitators. Ours is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 66 publications
(121 reference statements)
1
51
0
Order By: Relevance
“…Facilitation has been an effective and oft‐used implementation strategy, especially for CCMs. While specific mechanisms of facilitation effectiveness are still largely unknown, 26,59 facilitation is thought to be effective because facilitators have a diverse array of skills that allow for flexibility in accommodating site needs as they change over time and encouraging organizational learning 30,59,60 . With few notable exceptions, 61‐63 few studies have compared the effectiveness of different forms of facilitation, or examined whether this comparative effectiveness is moderated by organizational characteristics or earlier implementation progress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facilitation has been an effective and oft‐used implementation strategy, especially for CCMs. While specific mechanisms of facilitation effectiveness are still largely unknown, 26,59 facilitation is thought to be effective because facilitators have a diverse array of skills that allow for flexibility in accommodating site needs as they change over time and encouraging organizational learning 30,59,60 . With few notable exceptions, 61‐63 few studies have compared the effectiveness of different forms of facilitation, or examined whether this comparative effectiveness is moderated by organizational characteristics or earlier implementation progress.…”
Section: Discussionmentioning
confidence: 99%
“…While specific mechanisms of facilitation effectiveness are still largely unknown, 26,59 facilitation is thought to be effective because facilitators have a diverse array of skills that allow for flexibility in accommodating site needs as they change over time and encouraging organizational learning. 30,59,60 With few notable exceptions, [61][62][63] few studies have compared the effectiveness of different forms of facilitation, or examined whether this comparative effectiveness is moderated by organizational characteristics or earlier implementation progress. Our results, however, suggested that sites that were further along in the implementation process benefitted differently-and, in fact, less-from more intensive EF/IF than sites that were further behind.…”
Section: Early Adoption As a Moderator Of Implementation Strategy Ementioning
confidence: 99%
“…To explore patterns in the data, MJR created Excel spreadsheet data displays for each skill [ 19 ] that the expert transferred, documenting, for each instance, the expert’s technique(s); date; trainee; site(s); primary target of the expert’s efforts (e.g., trainee, site leader, meeting attendees); and an abbreviated summary of what the expert was helping trainees learn. Using these data displays, she explored patterns in how facilitators were interacting with each other and with site stakeholders, as well as changes in the level of intensity with which interactions occurred over time.…”
Section: Methodsmentioning
confidence: 99%
“…The integrated-Promoting Action on Research Implementation in Health Services (i-PARIHS) framework posits that facilitation is the active ingredient in the implementation process; facilitators need to assess and respond to the characteristics of the innovation being implemented, the individuals and teams involved in or affected by innovation implementation, and the organizational context [ 1 , 18 ]. Thus, facilitators need a wide range of very complex skills [ 19 ]. Lack of these skills can compromise fidelity to the facilitation intervention and ultimately has a negative effect on outcomes [ 20 – 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation